The effect of the National Health Insurance Scheme (NHIS) on health service delivery in mission facilities in Ghana: a retrospective study. Issue 1 (December 2016) - Aryeetey, Genevieve; Nonvignon, Justice; Amissah, Caroline; Buckle, Gilbert; Aikins, Moses
Abstract Background In 2004, Ghana began implementation of a National Health Insurance Scheme (NHIS) to minimize out-of-pocket expenditure at the point of use of service. The implementation of the scheme was accompanied by increased access and use of health care services. Evidence suggests most health facilities are faced with management challenges in the delivery of services. The study aimed to assess the effect of the introduction of the NHIS on health service delivery in mission health facilities in Ghana. We conceptualised the effect of NHIS on facilities using service delivery indicators such as outpatient and inpatient turn out, estimation of general service readiness, revenue and expenditure, claims processing and availability of essential medicines. We collected data from 38 mission facilities, grouped into the three ecological zones; southern, middle and northern. Structured questionnaires and exit interviews were used to collect data for the periods 2003 and 2010. The data was analysed in SPSS and MS Excel. Results The facilities displayed high readiness to deliver services. There were significant increases in outpatient and inpatient attendance, revenue, expenditure and improved access to medicines. Generally, facilities reported increased readiness to deliver services. However, challenging issues around high rates of non-reimbursement of NHIS claims due to errors in claims processing, lack of feedback regarding errors, and lack of clarity on claims reporting procedures were reported. Conclusion The implementation of the NHIS saw improvement and expansion of services resulting in benefits to the facilities as well as constraints. The constraints could be minimized if claims processing is improved at the facility level and delays in reimbursements also reduced.